Freight Management System Financial: Disbursement, Budget Management, Collection, General Ledger, Accounts Payable & Accounts Receivable: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The FMS helps in the proper management of financial resources, budgeting, accounting, andreporting of financial transactions. In this research, the focus is on analyzing the impact ofFMS on the financial performance of organizations. The study aims to identify the factors thatinfluence the implementation of FMS and how the implementation of FMS affects the financialperformance of organizations. Focuses on the development and implementation of acorporate financial management system. This system's objective is to give stakeholders andbusiness owners accurate and timely financial information so they can make defensibledecisions. The study examines current financial management systems in-depth and identifiesthe essential characteristics and capabilities needed for a successful system.The study showed that the implementation of FMS had a positive impact on the financialperformance of organizations. The organizations that implemented FMSs had better financialperformance indicators such as profitability, liquidity, and efficiency compared to those that didnot implement FMs. The study also revealed that factors such as organizational culture,management support, and technical expertise had a significant influence on theimplementation of FMs.The study findings suggest that the implementation of FMS can significantly improve thefinancial performance of organizations. The FMS enables organizations to have better controland management of financial resources, accurate financial reporting, and efficient budgeting.The study also highlights the importance of factors such as organizational culture,management support, and technical expertise in the successful implementation of FMs.Therefore, organizations need to consider these factors before implementing FMS to ensurethe successful implementation and optimal benefits of FMs.
Keywords: IT & Management